Diverse sensor responses from two functionalized tris(phthalocyaninato)europium ambipolar semiconductors towards three oxidative and reductive gases. Issue 2 (19th December 2018) - Liu, Shanshan; Wang, Haoyuan; Wang, Xiangyang; Li, Shaoren; Liu, Heyuan; Chen, Yanli; Li, Xiyou
Abstract : The first sensor array consisting of two ambipolar triphthalocyanines for sensitive detection and discrimination of three toxic gases with ultralow concentrations. Abstract : Ambipolar tris(phthalocyaninato) rare earth semiconductors, Eu2 [Pc(OC8 H17 )8 ]2 [Pc(OCH2 CF3 )8 ] (1 ) and Eu2 {Pc[(OC2 H4 )3 OCH3 ]8 }2 [Pc(OCH2 CF3 )8 ] (2 ), are synthesized and fabricated into well-organized films via a Langmuir-Shäfer (LS) method. Driven by intermolecular π–π stacking, as well as hydrophilic–hydrophobic interactions, 1 and2 aggregated in different modes, H for1 and J for2, in LS films. Consequently, higher conductivity and carrier mobilities for electrons and holes in the LS films of1 are achieved compared to those of2, with gate-induced sheet electron and hole densities ( n e and n h ) of 2.48 × 10 12 and 8.31 × 10 9 cm −2 for1, and 1.77 × 10 12 and 8.01 × 10 10 cm −2 for2, respectively. Comparative studies on the gas sensing behavior of the LS films of1 and2 revealed that, towards oxidative NO2, both1 and2 show n-type sensing behavior, with a higher sensitivity of2 (54.6% ppm −1 ) than1 (12.5% ppm −1 ) in the 0.10–0.85 ppm range, which can be attributed to the lower n e of2 . Unexpectedly, towards reductive NH3 (3.0–7.0 ppm) and H2 S (5.0–9.0 ppm), only ambipolar1 exhibits current responses, determined by the lower n h of1 . More importantly, the current of1 responds reversely towards NH3 and H2 S (decreases vs. increases) even though they are both reductive gases. This is because weakly reductive NH3 reduces n h while strongly reductive H2 S increases n e . By combining the distinct response patterns of ambipolar1 and2, these three toxic gases can be distinguished unambiguously from each other, showing the potential for these two molecules in efficient chemiresistor sensor arrays.